2014
DOI: 10.1073/pnas.1409284111
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary origin of insect– Wolbachia nutritional mutualism

Abstract: Obligate insect-bacterium nutritional mutualism is among the most sophisticated forms of symbiosis, wherein the host and the symbiont are integrated into a coherent biological entity and unable to survive without the partnership. Originally, however, such obligate symbiotic bacteria must have been derived from free-living bacteria. How highly specialized obligate mutualisms have arisen from less specialized associations is of interest. Here we address this evolutionary issue by focusing on an exceptional insec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
407
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 374 publications
(437 citation statements)
references
References 45 publications
15
407
2
1
Order By: Relevance
“…The ease of maintaining bed bugs in laboratory cultures, and the availability of isolated populations and museum specimens makes C. lectularius an excellent model organism for the study of the origins and maintenance of mitochondrial heteroplasmy. C. lectularius may also contribute to a better understanding of the roles of environmental factors (e.g., temperature, starvation, Wolbachia infection; Nikoh et al 2014] in facilitating, maintaining, and purging paternal mtDNA. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ease of maintaining bed bugs in laboratory cultures, and the availability of isolated populations and museum specimens makes C. lectularius an excellent model organism for the study of the origins and maintenance of mitochondrial heteroplasmy. C. lectularius may also contribute to a better understanding of the roles of environmental factors (e.g., temperature, starvation, Wolbachia infection; Nikoh et al 2014] in facilitating, maintaining, and purging paternal mtDNA. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Histological analyses were conducted as described (28,71). Symbiont genome sequencing and annotation were performed as described (72)(73)(74)(75). Transcriptomic data of the host bacteriomes were obtained by RNA sequencing using TruSeq RNA Sample Preparation Kit v2 (Illumina) and HiSeq2000 sequencer (Illumina), and analyzed using the program Trinity (76) implemented in the MASER pipeline (cell-innovation.nig.ac.jp/).…”
Section: Methodsmentioning
confidence: 99%
“…Two examples that have caught the attention of evolutionary biologists involve the bedbug Cimex lectularius (Hosokawa et al, 2010;Nikoh et al, 2014) and the parasitic wasp Asobara tabida (Dedeine et al, 2001). In the bedbug C. lectularius, Wolbachia fullfils a role of dietary provisioner of vitamin B (Hosokawa et al, 2010) and biotin (Nikoh et al, 2014). Hosokawa and colleagues found that reduction or elimination of Wolbachia through antibiotic treatment rendered animals incapable of producing normally developing eggs, which could be restored by dietary supplementation of vitamin B.…”
Section: Wolbachia As Obligate Mutualistsmentioning
confidence: 99%
“…Such sexual asymmetry in favor of females is similar in principle to that between mitochondrial and nuclear genomes, where mitochondrial DNA (mtDNA) mutations can be maintained when favorable in females, even if they are harmful in males (Gemmell et al, 2004). Wolbachia-host associations therefore provide an opportunity to explore the coevolutionary processes that concur with intracellular lifestyles (Sicard et al, 2014) with new knowledge of Wolbachia biology coming from bacterial genome analysis (e.g., Wu et al, 2004;Ellegaard et al, 2013;Nikoh et al, 2014;Ramírez-Puebla et al, 2015).…”
Section: Introductionmentioning
confidence: 99%